External Quality Assessment in Laboratory Safety Area (PNAEQ-1S Segurança Laboratorial 2023) - Ventura, Catarina (2023)
Introduction: The National External Quality Assessment Program (PNAEQ) provides tools for carrying out external quality assessment in Laboratory Safety area. These tools allow the identification of occurrences and/or critical points in the operation, installations or equipment, that could have impact on the safety of patients and workers, beyond prioritize the necessary improvement actions. Objective: Presentation of the methodology implemented in PNAEQ in 2023, for the External Quality Assessment (EQA) in Laboratory Safety area.